Establishment and analysis of tissue and fast-growing normal root cultures of four Gentiana L. species, rare highland medicinal plants - Drobyk, N.M.; Mel'nyk, V.M.; Hrytsak, L.R.; Kravets, N.B.; Konvalyuk, I.I.; Twardovska, M.O.; Kunakh, V.A. (Вiopolymers and Cell, 2018)
Aim. To obtain tissue and isolated root cultures of four Gentiana L. species from Ukraine (G. lutea L., G. punctata L., G. acaulis L. and G. asclepiadea L.) and study peculiarities of their growth and content of flavonoids and xanthones. Methods. In vitro culture, chromatography, spectrophotometry and statistical methods. Results. The conditions were developed for callus induction, proliferation, and long-term maintenance of fast-growing root cultures from gentians. A comparative study of total flavonoid and xanthone content in the cultured tissues, isolated cultured roots and wild plants of gentians was carried out. The capacity was ascertained for synthesizing these biologically active substances in vitro. The content of compounds varied both in calli and isolated roots derived from the plants of different gentian species, and in tissue and organ cultures of these species. The morphogenic and non-morphogenic cultures showed much lower flavonoid and xanthone content than the shoots of intact plants, but similar to that of natural roots. The fast-growing normal root cultures displayed higher concentrations of these biologically active compounds than the callus tissues in most cases. Conclusions. A high yield of biomass from gentian cultures in vitro and their ability to synthesize and accumulate flavonoids and xanthones make them as a promising source of these biologically active compounds.